The Influence of Entrepreneurial Leadership on Employee Performance with the Role of Mediation of Organizational Culture and Teamwork in the Property Industry of PT. Panasia Griya Mekarasri - Agustina Nancy Oktavia; Endi Sarwoko; Eric Harianto (Jurnal Indonesia Sosial Teknologi, 2025)
This research aims to examine the influence of entrepreneurial leadership on employee performance with organizational culture and teamwork as mediating variables. This research uses quantitative methods with a survey approach, involving 43 employees of PT. Panasia Griya Mekarasri was selected using purposive sampling. Data will be collected through a questionnaire with a 5-point Likert Scale and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The research results reveal that Entrepreneurial Leadership has no impact on employee performance, Entrepreneurial Leadership has a positive and significant influence on organizational culture, Entrepreneurial Leadership has a positive and significant influence on teamwork, Organizational culture has a positive and significant influence on employee performance, Collaboration teams have a positive and significant influence on employee performance, Teamwork positively mediates the influence of Entrepreneurial Leadership on employee performance, Teamwork positively mediates the influence of Entrepreneurial Leadership on employee performance.